Sustainable fashion management: Behrens Secondhand Space (Research, Society and Development, 2024)
This study looked at Espaço Behrens, a luxury thrift store, focusing on its development over time in aspects such as financial management, marketing strategies, operational quality and social and environmental responsibility initiatives. In the operational sphere, Espaço Behrens adopted quality tools and directed efforts towards developing its online presence, investing in an intuitive website, digital marketing strategies and partnerships with influencers. Espaço Behrens' community outreach project was highlighted as a comprehensive initiative, aimed at extending the company's benefits beyond the commercial aspect. The pursuit of social and environmental responsibility, combined with solid financial commitment, highlights Espaço Behrens as an agent of positive change in the community. The marketing and quality development of Espaço Behrens reflects remarkable progress in building a strong brand in the second-hand luxury fashion market. The general objective of the topic covered was to analyze the quality standard of services provided by Second Hand and the application of marketing. And the methodology is characterized as a community extension project, with qualitative methodology. The company has adopted innovative strategies, exclusive collaborations, and sustainable practices to consolidate its position as an innovative luxury thrift store aligned with the expectations of the modern consumer. The work provides a comprehensive overview of Espaço Behrens, highlighting its commitment to operational excellence, marketing innovation, financial integrity and social responsibility, elements that contribute to the company's success and positive impact on the second-hand luxury fashion trade scene.